Report of a sample survey of unemployment among 1977 school leavers - Ministry of economic planning, statistics division (Ibadan : Ministry of economic planning, 1977)
This is the report of the statistics division of the ministry of Economic planning publishes annually the report of a sample survey of unemployment among school leavers from the primary, secondary modern and secondary grammar schools in Oyo state.
ahz 04/04/2019
Arch
Keywords: Employment; Unemployment; Economic planning; Nigeria